2012
DOI: 10.1111/j.1365-2958.2012.08011.x
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic Escherichia coli system identifies a conserved origin tethering factor in Actinobacteria

Abstract: SummaryIn eukaryotic and prokaryotic cells the establishment and maintenance of cell polarity is essential for numerous biological processes. In some bacterial species, the chromosome origins have been identified as molecular markers of cell polarity and polar chromosome anchoring factors have been identified, for example in Caulobacter crescentus. Although speculated, polar chromosome tethering factors have not been identified for Actinobacteria, to date. Here, using a minimal synthetic Escherichia coli syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 44 publications
(70 reference statements)
3
93
1
Order By: Relevance
“…Fitting with this, our experiments indicated that the C-terminal domain is the interaction module for RacA, which is a soluble cytoplasmic protein. It was recently reported that the interaction of C. glutamicum ParB, which is a chromosome-binding protein like RacA, with its cognate DivIVA requires central regions of the C-terminal domain as well (9). Our results thus confirm earlier speculations that the sporulation and the division functions of DivIVA can be separated.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Fitting with this, our experiments indicated that the C-terminal domain is the interaction module for RacA, which is a soluble cytoplasmic protein. It was recently reported that the interaction of C. glutamicum ParB, which is a chromosome-binding protein like RacA, with its cognate DivIVA requires central regions of the C-terminal domain as well (9). Our results thus confirm earlier speculations that the sporulation and the division functions of DivIVA can be separated.…”
Section: Discussionsupporting
confidence: 82%
“…Membrane binding and curvature sensitivity appear to be intrinsic features of DivIVA, as it was shown that DivIVA of Bacillus subtilis also localizes to curved membranes when expressed in other, nonrelated species, including yeast cells (4). DivIVA is used as a scaffold and recruits other proteins that function in cell division, cell wall biosynthesis, secretion, genetic competence, or chromosome segregation (5)(6)(7)(8)(9)(10)(11)(12)(13). The proteins that interact with DivIVA are therefore diverse and comprise both transmembrane and cytosolic proteins (14).…”
mentioning
confidence: 99%
“…It is conceivable that the nucleation of ParA at the tip of the aerial hyphae depends on the TIPOC. Indeed, interaction between Streptomyces DivIVA and ParB has been demonstrated, albeit in the heterologous host E. coli (38). We have also shown that localization of FtsZ was compromised in the scy mutant (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…In B. subtilis, LCP proteins were found to interact with MreB, a cytoskeleton protein which is probably responsible for their localization (6). The localization of the LCP proteins in C. glutamicum suggests that, analogous to MreB/Tag-TUV in B. subtilis, they might be part of the elongasome, which is required for polar growth, and be spatially organized by DivIVA (17,(36)(37)(38). However, given that C. glutamicum lacks MreB and that the cytoplasmic part of LcpA is dispensable for function, the localization likely appears within the membrane or in the periplasm, and additional proteins would be required to connect it to the elongasome.…”
Section: Discussionmentioning
confidence: 99%